The lord of the rings : adventure book game [games] - Tolkien, J. R. R. (John Ronald Reuel), 1892-1973; Little, Jason; Ross, Marcus; Rodriguez, Vlad (Adventure book game, 2023)
"Sauron's shadow has fallen across Middle-earth, and the One Ring must be destroyed. Leave the Shire's green pastures to travel to fair Rivendell, survive the Mines of Moria, march on Isengard, and finally reach Morodor. Only by working together can you ensure the One Ring is delivered to the fiery heart of Mount Doom and destroy it once and for all"--Box.